Keeping it Simple-Efficiency Costs of Fixed Margin Regimes in Transfer Pricing - Beer, Sebastian (IMF Working Papers; Working Paper ;, 2022)
Simplifying tax policy comes with costs and benefits. This paper explores simplification options for the taxation of MNEs, an area where administrative and compliance costs of the current rules are large. Simplified approaches seek to reduce these costs by relying on an approximation of the true tax base, potentially distorting resource allocation. We examine the efficiency cost of transfer pricing simplification theoretically and empirically. Using a sample of 300,000 firms located in 22 countries, we estimate that common transfer pricing practices reduce efficiency between 0.25 and 2.2 percent of total factor productivity across sectors. Focusing on the manufacturing sector, we then observe that simplification more than doubles sectoral inefficiency on average. However, large differences exist, with moderate efficiency costs in several sectors.